Thermal investigation of solid 2-methoxycinnamylidenepyruvate of some bivalent transition metal ions - Carvalho, C. T.; Caires, Flavio J. [UNESP]; Lima, L. S. [UNESP]; Ionashiro, Massao [UNESP] (Springer, 2012)
Solid-state M-2-MeO-CP compounds, where M represents bivalent Mn, Fe, Co, Ni, Cu, Zn and 2-MeO-CP is 2-methoxycinnamylidenepyruvate, were synthesized for the first time. Simultaneous thermogravimetry and differential thermal analysis, differential scanning calorimetry, X-ray powder diffractometry, infrared spectroscopy, TG-FTIR system, elemental analysis and complexometry have been used to characterize and to study the thermal behaviour of the compounds. The dehydration in all the compounds, except for iron occurs in a single step. The thermal decomposition of the anhydrous compounds occurs in two or three steps with the formation of the respective oxides, Mn3O4, Fe2O3, Co3O4, NiO, CuO and ZnO, as final residue. The results also provided information concerning the thermal behaviour and identification of the gaseous products evolved during the heating of these compounds.
Keywords: Bivalent transition metals; 2-methoxycinnamylidenepyruvate; Thermal behaviour